Nexus between Issue of Environmental Pollution and the Urban Population: Evidence of Economic Growth in Indonesia - Qodri, Lutfi Asnan; Tri Wahyudi, Setyo (Journal of Economics Research and Social Sciences, 2021)
This study aims to analyze the factors that cause climate change that occurs in Indonesia. From every effort to increase economic growth, some elements are sacrificed. The Oil Palm Industry, high levels of CO2 emissions, Gini ratio index, and population increase in urban areas are variables used in this research. This research was conducted for thirty years, from 1990 to 2020. The analysis model used was the Vector Error Correction Model (VECM). The estimation results show that the palm oil industry, the impact of CO2 emissions, and the increase in urban population have a positive effect in the long term but do not impact economic growth in the long term because one of them is environmental quality degradation. Therefore, sometimes every effort to increase economic growth must be accompanied by mitigation of environmental impacts that will affect the short and long term.